BEING Tech-savvy Is Not Enough: Preparing Future Reflective EFL Practitioners for Technology Integration in Teaching - Elis Homsini Maolida; Didi Suherdi; Pupung Purnawarman (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
As part of a larger research on EFL student teachers’ TPACK development, this study explores a preparation program aimed to train EFL student teachers to be technology savvy and at the same time develop their skill on technology integration in teaching English through reflective based activities. It involved 42 EFL student teachers and a teacher educator in 16 weeks learning interaction that focused on technology integration for classroom purpose. A case study design was utilized by obtaining data from observation of online classroom interaction, semi-structured interview with the teacher educator and the student teachers and documents of student teachers’ submitted tasks. The data were thematically analysed to reveal types of reflection-based activities employed to develop EFL student teachers’ competence in integrating technology in teaching English and their responses toward the activities. The findings reveal that at least four reflection-based activities (lesson design, digital story, reading reflection and reflection during the learning) were employed to foster the student teachers’ skill of technology integration in teaching English. Despite some challenges in their enactment, the reflection-based activities were positively responded as indicated by the EFL student teachers’ active participation in online classroom interaction and their positive views regarding reflection-based activities. Keywords: Reflective Practitioner, reflection, technology integration, EFL student teachers